Os falares da Bahia e do Espírito Santo : implicações sob os aspectos dialetológicos - Aurélio, Renato Pereira (2012)
This study consists on a research in the area of dialects conducted within the Linguistic Geography. Thus it is made an approach about the constitution of Dialectology, with emphasis on studies implemented in Brazil, in the period pregeolinguistic and the four phases of dialect studies in the country, all of them fundamental to the proposition of the Project Alib. The study provides an overview of the Brazilian linguistic atlas published and in progress in Brazil, including the Atlas of Early “Baianos” Speeches (APFB) and the Linguistic Atlas of the Espírito Santo State (ALES), whose letters are compared to check the possible influence of Bahia on the other state. Considering that the study is based on an analysis of the letters of lexical atlas mentioned, as well as others which record the lexias selected, it is also discussed a little about the relationship between lexicon and culture. There is a brief description of theconstitution of Espírito Santo State, the process of colonization and settlement. The hypothesis of the study is based on Zagari’s postulates (2005), which notes the occurrence of speeches from Bahia in north of Minas Gerais and Rodrigues (2008), who discusses the possibility of revising the classification made by Nascentes (1953) to the Brazilian dialects, verifying the occurrence of lexias mentioned by Rossi (1963) in Espírito Santo territory. In the analysis and discussion are presented the results of the comparison of eight pairs of lexical letters adapted from APFB (ROSSI, 1963) and ALES (RODRIGUES, 2008), considering that five pairs reveal the common occurrences in other atlas and three pairs characterize a possible “Bahiana” influence in the speech of Espirito Santo natives.